Exploring Adaptive Feedback Strategies in Competency-Based Medical Education - Davoudi, Shirin; Eskandari, Bahram (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore how clinical educators employ adaptive feedback strategies within the framework of competency-based medical education (CBME) to enhance learner development and performance. This qualitative study employed a phenomenological approach to investigate the experiences of clinical educators in CBME programs. Semi-structured interviews were conducted with 31 faculty members from various medical disciplines in Tehran, selected through purposive sampling. Data collection continued until theoretical saturation was achieved. All interviews were transcribed verbatim and analyzed using thematic analysis, following Braun and Clarke’s six-phase framework. Nvivo software was used to facilitate data management and coding. The analysis focused on identifying patterns and strategies used by educators to tailor feedback in diverse clinical and educational contexts.Three main themes emerged: (1) Personalization of feedback, which included strategies such as emotional sensitivity, alignment with milestones, and tailoring feedback based on individual learner needs; (2) Contextual influences on feedback, which encompassed environmental constraints, institutional culture, and hierarchical dynamics that shaped feedback delivery; and (3) Developmental impact on learners, highlighting how adaptive feedback fostered motivation, self-regulation, and feedback-seeking behavior. Participants emphasized the importance of empathy, trust, and situational judgment in feedback practices, while also noting barriers such as time pressure and lack of formal feedback training. Adaptive feedback is a dynamic, context-sensitive process that plays a critical role in the success of CBME. Clinical educators utilize a range of strategies to tailor feedback based on learner characteristics, contextual demands, and developmental goals. Supporting these practices through institutional policy, faculty development, and cultural change is essential for fostering meaningful learning and competency progression in medical education.